Effects of Human Adipose-Derived Stem Cells in Regenerating the Damaged Renal Tubular Epithelial Cells in an Animal Model of Cisplatin-Induced Acute Kidney Injury - Saeyoon Kim; Eung Bin Lee; In Hwan Song; Yong Jin Kim; Hosun Park; Yong Woon Kim; Gi Dong Han; Kyung Gon Kim; Yong Hoon Park (Korean Society of Pediatric Nephrology, 2015)
Background: We conducted this experimental study to examine whether human adipose-derived stem cells (ADSCs) are effective in achieving a recovery of damaged renal tubular epithelial cells in an animal model of cisplatin-induced acute kidney injury using rats. Methods: To examine the in vitro effects of ADSCs in improving nephrotoxicity, we treated mouse renal tubular epithelial cells with both ADSCs and cisplatin mouse renal tubular epithelial cells. And we equally divided 30 male white Sprague-Dawley (SD) rats into the three groups: the control group (intraperitoneal injection of a sterile saline), the cisplatin group (intraperitoneal injection of cisplatin) and the ADSC group (intraperitoneal injection of cisplatin and the hADSC via the caudal vein). At five days after the treatment with cisplatin, serum levels of blood urine nitrogen (BUN) and creatinine were measured from each SD rat. We performed histopathologic examinations of tissue samples obtained from the kidney. Results: The degree of the expression of TNF-α and that of Bcl-2 were significantly higher and lower respectively, in cisplatin group (P<0.05). Serum levels of BUN (P=0.027) and creatinine (P=0.02) were significantly higher in cisplatin group. On histopathologic examinations, there was a significant difference in the ratio of the renal injury between cisplatin group and ADSC group (P=0.002). Conclusion: The ADSCs might have a beneficial effect in regenerating the damaged renal tubular epithelial cells.